2021
DOI: 10.37190/ppmp/133288
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes of glass bead particles upon an abrasive blasting as characterized by settling and flotation experiments

Abstract: The recent developments in mineral processing led researchers to look for alternative methods and propose new mechanisms for enhancing the efficiency of relatively costly processes (e.g., flotation, aggregation), where especially dealing with fine particles. Finer the particles, the higher the role of their surface on their behavior and properties. The importance of particle morphology becomes even clearer when particle-particle and particle-bubble interactions are considered. In this study, the effect of part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Even though many papers reported the effects of different parameters such as grinding type and blasting (Ulusoy et al, 2003;Yekeler et al, 2004;; Ulusoy, U., 2019; Ulusoy, U., 2018; Hassas et al, 2021), ball size (Kim et al, 2019) on morphological characteristics of minerals, to our knowledge, only a few studies reported the effect of grinding time (Ulusoy and Bayar, 2022;Guven et al, 2020;Uysal et al, 2021; on afore-mentioned indices.…”
Section: Morphological Characteristics Of Particlesmentioning
confidence: 99%
“…Even though many papers reported the effects of different parameters such as grinding type and blasting (Ulusoy et al, 2003;Yekeler et al, 2004;; Ulusoy, U., 2019; Ulusoy, U., 2018; Hassas et al, 2021), ball size (Kim et al, 2019) on morphological characteristics of minerals, to our knowledge, only a few studies reported the effect of grinding time (Ulusoy and Bayar, 2022;Guven et al, 2020;Uysal et al, 2021; on afore-mentioned indices.…”
Section: Morphological Characteristics Of Particlesmentioning
confidence: 99%